Protected Employment in favor of people with disabilities in the Ecuadorian private sector - Arteaga Moreira, Ana Jessenia (2023)
Sheltered Employment is one of the positive action measures adopted in order to achieve the labor inclusion of people with disabilities through the Special Employment Centers (CEE). The objective of the study was to analyze the implementation of Sheltered Employment as an instrument of access to employment for people with disabilities in the private sector in Ecuador. The methodology used was qualitative, oriented mainly to the description, understanding, interpretation and justification of the Ecuadorian legal situation, compared with the Spanish and Chilean doctrine and legislation. The results showed that, in Ecuador, the Sheltered Employment mechanism is still unknown and the reserve quota of 4% prevails in ordinary employment for people with disabilities, which leads to hiring that merely complies with legal obligations and does not guarantee work. worthy. The lack of CEE is attributed to the absence of tax incentives and inclusion policies by the State, thus limiting the development of adequate labor inclusion in both the private and public sectors. However, the EWCs seek the equitable labor integration of people with disabilities, promoting their economic and social sustainability through the development of skills.